1993
DOI: 10.21273/horttech.3.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic Problems in Cultivated Liriopogons

Abstract: Liriopogons (Liriope, Ophiopogon) are versatile landscape plants with a complexity of taxonomic problems. A taxonomic revision of liriopogons cultivated in the United States is needed; one that includes an inventory of taxa, quantitative descriptions of species and cultivars, keys and other aids for segregation and identification of taxa, documentation of taxa with vouchers deposited in herbaria, and establishment of a living germplasm collection that can serve as a standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Having two cytotypes of 'Aphrodite' and 'Minerva' in the cultivar collection could represent a reversion to the tetraploid state over many years of propagation. However, nursery practices, including sexual propagation of cultivars, cultivar substitution, mislabeling, and seedling invasion of stock plants, have been shown to degrade cultivar collections in previous studies (Fantz, 1994). Confirming a previous report by Van Huylenbroeck et al (2000), 'Pink Giant' was found to be a hexaploid at 6.97 ± 0.07 pg (Table 1).…”
Section: Methodssupporting
confidence: 85%
“…Having two cytotypes of 'Aphrodite' and 'Minerva' in the cultivar collection could represent a reversion to the tetraploid state over many years of propagation. However, nursery practices, including sexual propagation of cultivars, cultivar substitution, mislabeling, and seedling invasion of stock plants, have been shown to degrade cultivar collections in previous studies (Fantz, 1994). Confirming a previous report by Van Huylenbroeck et al (2000), 'Pink Giant' was found to be a hexaploid at 6.97 ± 0.07 pg (Table 1).…”
Section: Methodssupporting
confidence: 85%
“…2). Morphological approaches alone are incapable of differentiating the ≈100 named cultivars (Fantz, 1993), underscoring the value of a molecular marker approach for identifi cation.…”
Section: Discussionmentioning
confidence: 99%
“…Liriopogons are native to China, India, Japan, Korea, the Philippines, and Vietnam with Liriope consisting of approximately eight species (Chen and Tamura, 2000a) and Ophiopogon consisting of 65 species (Chen and Tamura, 2000b). Popularity of liriopogons is attributable, in part, to their adaptability (Li et al, 2011) and versatility in the landscape, easily filling the roles of groundcovers, foundation plants, edging and massing plants, and understory plants (Fantz, 1993).…”
mentioning
confidence: 99%
“…The following centuries resulted in many genera designations (Anemarrhena Bunge, Chloopsis Blume, Convallaria L., Flueggea Rich., Liriope, Mondo Adans., Ophiopogon, Polygonastrum Moench, and Slateria Desv.) and common names (aztec grass, bordergrass, lilyturf, liriope, mondo grass, monkeygrass, and snakesbeard) (Fantz, 1993;Nesom, 2010). Nevertheless, liriopogons' attractiveness, resistance to pests and diseases, hardiness, and utility in the landscape have made them important nursery crops.…”
mentioning
confidence: 99%